Eugenics in New Zealand 1900-1940 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Fleming, Philip J (Massey University, 1981)
No abstract. The following taken from introduction: From approximately 1900 social workers, doctors, biologists and legislators throughout the Western world began in increasing numbers to direct their attention to eugenics, an applied 'science' which aimed at improving the genetic potentialities of the human species. As the new creed gained respect and as individuals, many of them in the front-line of the health and social services, sought an explanation for society's ills and a means of curing them, eugenic societies sprung up in many countries, assuming a different character wherever they took root. This thesis is a history of eugenics in New Zealand and it traces the development of eugenic thought from the early years of the twentieth century through to the 1930s when the subject experienced a brief revival of interest. By this time, however, eugenics had been deserted by the scientific establishment, who now realized that much of earlier eugenics propaganda was little more than unsubstantiated prejudice, and the creed was soon to be irreparably discredited by the demonstration of perverted eugenics in Nazi Germany. In tracing the history of eugenics in New Zealand attention is directed to the work of local writers on eugenics, to the role of politicians and to the activities of the New Zealand Eugenics Education Society. The Society was formed in Dunedin in 1910, three years after its parent body had been established in London, but despite the formation of other branches in Wellington, Christchurch and Timaru, the local Society persisted for less than four years. Interest in eugenics, at least in certain sectors of the population, remained high, however, and its role in a variety of issues which arose during the 1920s is examined. This agitation culminated in the 1924 Committee of Inquiry into Mental Defectives and Sexual Offenders and, four years later, the Mental Defectives Amendment Bill. In discussing the revival of interest in eugenics during the 1930s a case study of discussion on the subject in the Women's Division of the New Zealand Farmers' Union offers an insight into the mechanics of agitation and the issues raised by the topic
Keywords: Eugenics